Gezin dat leeft van het schillen van eiken. Uit: De Prins der geïllustreerde bladen, jg. XI, p.295 - Tepe, R., (1912)
Gezin dat leeft van het schillen van eiken. Uit: De Prins der geïllustreerde bladen, jg. XI, p.295.